Tuned mass damper effects on the tendon responses of a novel 10 MW multi-body floating offshore wind turbine platform - Yang, Yang; Bashir, Musa B.; Sakaris, Christos S.; Loughney, Sean; Wang, Jin; Michailides, Constantine; Li, Chun (My University, 2021)
This paper presents a study on the mitigation of dynamic responses of a spar-type multi-body platform of a Floating Offshore Wind Turbine (FOWT) under coupled wind-wave-current loadings. The multi-body floating platform was developed to support a 10 MW wind turbine under investigation. The mitigation is achieved by implementation of a structural control module based on Tuned Mass Damper (TMD). A fully-coupled tool based on AQWA and FAST is developed and used to perform numerical analysis of the FOWT. The time-varying tension of the tendons due to turbulent wind and irregular wave loadings are compared for the scenarios with and without TMD. The results indicate that tensions of the tendons are effectively reduced by the TMD. An average reduction of 11.8% on the Damage Equivalent Load (DEL) is achieved for the tendons. The alleviation on the tension fluctuation is beneficial in extending the service lifetime of the tendons.
Keywords: Offshore oil well production; Offshore wind turbines; Structural dynamics; Vibration control